Deceleration processes of secondary electrons produced by a high-energy Auger electron in a biological context. (1st November 2016) - Kai, Takeshi; Yokoya, Akinari; Ukai, Masatoshi; Fujii, Kentaro; Watanabe, Ritsuko
Abstract: Purpose: To simulate the deceleration processes of secondary electrons produced by a high-energy Auger electron in water, and particularly to focus on the spatial and temporal distributions of the secondary electron and the collision events (e.g. ionization, electronic excitation, and dissociative electron attachment) that are involved in the multiplication of lesions at sites of DNA damage. Materials and methods: We developed a dynamic Monte Carlo code that considers the Coulombic force between an ejected electron and its parent cation produced by the Auger electron in water. Thus our code can simulate some return electrons to the parent cations. Using the code, we calculated to within the order of femtoseconds the temporal evolution of collision events, the mean energy, and the mean traveling distance (including its spatial probability distribution) of the electron at an ejected energy of 20 eV. Results: Some of the decelerating electrons in water in the Coulombic field were attracted to the ionized atoms (cations) by the Coulombic force within hundreds of femtoseconds, although the force did not significantly enhance the number of ionization, electronic excitation, and dissociative electron attachment collision events leading to water radiolysis. Conclusions: The secondary electrons are decelerated in water by the Coulombic force and recombined to the ionized atoms (cations). Furthermore, the some return electrons might be prehydrated in water layer near the parent cation in DNA if the electrons might be emitted from the DNA. The prehydrated electron originated from the return electron might play a significant role in inducing DNA damage.